Potret Intelektual Muslim: Sebuah Tinjauan Sosiologi Pengetahuan terhadap Pemikiran Ahmad Syafii Maarif - Putra, Arie (Masyarakat: Jurnal Sosiologi, 2013)
There are numerous Islamic actors whom undertook significant role in establishing Indonesian society understanding toward Islam. One of them is Ahmad Syafii Maarif, one of the Islamic figures who evokes Indonesian muslim optimism toward democracy. Through sociology of knowledge framework, this research will take a look on the formation process of Ahmad Syafii Maarif’s Islamic thought. Sociology of knowledge is considered to be the appropriate framework due to the interconnectivity it provided between historical, philosophical, and sociological framework in investigating knowledge formation. However, though being utilized in this research for its extensiveness, the framework tends to stress the connection between knowledge formation process and particular political and economic relations, making variables aside from the aforementioned aspects could not be incorporated comprehensively in the analysis. Therefore in this research more than other we will see how Ahmad Syafii Maarif’s Islamic thought being explored as cognitive responds toward the political and economic conditions which surrounding him.